PROCEDURE OF 3D CONFORMAL RADIOTHERAPY ON SQUAMOUS CELL CARCINOMA CASE IN ORBITAL REGION IN RADIOTHERAPY UNIT OF DR. SARDJITO YOGYAKARTA HOSPITAL - Nova Aditya Surya Irawan; Gatot Murti Wibowo; Khumaidi Khumaidi (Jurnal Imejing Diagnostik (JImeD), 2018)
Background: This study aims to determine the procedures, techniques, reasons and evaluation of 3D conformal radiotherapy of squamous cell carcinoma case in the orbital region with additional bolus that has been done in the Radiotherapy unit of Dr. Sardjito Yogyakarta Hospital. In addition, from this research also to find out how the visually tumor response to the radiation that has been given and there are limits of research for tumor responses made observations from the beginning of radiation to the completion of radiation.Methods: This type of research is qualitative with a case study approach. The data was collected in November-December 2017 at radiotherapy Unit of Dr. Sardjito Yogyakarta Hospital by observation methodology, interview with Radiation Oncologist Specialist, Medical Physicist and Radiographer. the data obtained from the study were analyzed by an interactive model, creating the interview transcripts subsequently reduced and processed within the type of open coding, given within the type of quotations then are often drawn conclusions.Results: The results showed that the 3D Conformal Radiotherapy of squamous cell carcinoma case on orbital region with the addition of a bolus in Dr. Sardjito Yogyakarta Hospital consists of a CT Simulator examination, TPS (Treatment Planning System), Verification and Treatment (radiation therapy). The bolus in the treatment process is intended for this case to provide a 95% dose to the target tumor raised up to the surface. For the response shown in this case the patient was not good despite the reduction in tumor, the tumor response was not good (response 50%) according to WHO criteria showed stable disease criteria (SD).Conclusion: 3D conformal radiotherapy of squamous cell carcinoma case in the orbital region of this patient with the addition of a bolus aims to obtain a homogeneous distribution of all tumor targets and for visual tumor response in this case according to WHO criteria showing stable disease (SD) criteria.